2022
DOI: 10.1002/jmv.28411
|View full text |Cite
|
Sign up to set email alerts
|

Changes in endemic patterns of respiratory syncytial virus infection in pediatric patients under the pressure of nonpharmaceutical interventions for COVID‐19 in Beijing, China

Abstract: A series of nonpharmaceutical interventions (NPIs) was launched in Beijing, China, on January 24, 2020, to control coronavirus disease 2019. To reveal the roles of NPIs on the respiratory syncytial virus (RSV), respiratory specimens collected from children with acute respiratory tract infection between July 2017 and Dec 2021 in Beijing were screened by capillary electrophoresis‐based multiplex PCR (CEMP) assay. Specimens positive for RSV were subjected to a polymerase chain reaction (PCR) and genotyped by G ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…The detection rate of RSV sharply dropped after an outbreak in January 2020 and stayed in a nearly dormant state during the next seven months. However, the detection rates from June to September of 2021 remained abnormally high (over 10%), as reported in Shanghai and Beijing ( Jia et al., 2022 ; Jiang et al., 2022 ). We also found higher proportions of RSV-infected children aged 1–3 years in 2021.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The detection rate of RSV sharply dropped after an outbreak in January 2020 and stayed in a nearly dormant state during the next seven months. However, the detection rates from June to September of 2021 remained abnormally high (over 10%), as reported in Shanghai and Beijing ( Jia et al., 2022 ; Jiang et al., 2022 ). We also found higher proportions of RSV-infected children aged 1–3 years in 2021.…”
Section: Discussionmentioning
confidence: 64%
“…A study in Argentina also showed that the delayed RSV upsurge was related to new viral variants ( Dolores et al., 2022 ). Epidemiological data in Beijing revealed abnormal RSV prevalence in the summer of 2021 along with the shift of subtypes from B to A ( Jiang et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…After the outbreak of COVID‐19, multiple non‐pharmaceutical interventions (NPIs), such as wearing masks, handwashing, self‐quarantine and lockdown have been implemented to prevent the spread of COVID‐19. However, the COVID‐19 pandemic and NPIs affected the prevalence of other respiratory pathogens, and there have been several reports of changes in RSV prevalence 24–26 . For example, a review reported that the expected epidemic peaks were not observed in the United States and Tokyo in 2020, but a resurgence occurred in 2021 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study in Beijing revealed that the implementation of non-pharmaceutical interventions (NPIs) reduced the incidence of RSV from 31.9% to 4.4% in children. 14 These lines of evidence support the likelihood of a "tripledemic" in China after lifting the "Zero COVID-19" policy.…”
Section: Additional Major Challenges Associated With Lifting the Zero...mentioning
confidence: 93%